Drug induced liver injury: a clinical perspective - Navarro, Victor (Henry Stewart Talks, 2009)
Definition of drug induced liver injury (DILI), Types and mechanisms of DILI, Safety withdrawals, Signals of DILI in drug development, Epidemiology of DILI, Clinical patterns, Hepatocellular liver injury, Cholestatic liver injury, What comprises liver injury?, Adaptation to injury, Toxicity grading in clinical trials, Jaundice, Common signatures of DILI, Susceptibility factors for DILI, Key elements in diagnosis, Causality assessment tools, Management of DILI, Monitoring in clinical practice